Pandangan Al-Qur’an Atas Peran Ayah Dalam Proses Perkembangan Anak (Kajian Tafsir Tematik) - Hasri, Muhammad Muads (el Buhuth: Borneo Journal of Islamic Studies, 2019)
This article discusses about Al-quran opinion on the role of father in develoment of the child. The focus of this study is to reveal the verses of Al-qur'an that relate to the role of father in the family. Furthermore, this article will also illustrate the story of the father in the Qur'an. This article is a library research with descriptive-analytic method. The lens of contemporary and classic tafsir paradigm are also used as the aproach to analyse the data. From the analysis that has been carried out, this research concludes several important remarks. Firts, the Qur'an shows a role that should be applied by a father in the development process of his children, one of which is by monitoring and controlling the daily lives of children, instilling educational values, building good closeness and communication with children, and providing support and direction well. Second, several verses in the Qur’an describe the role of fathers who have their own way of educating their children, so that the method is relevant to be applied in the present context, They are Luqman, Prophet Ibrahim, Prophet Nuh, and Prophet Ya'qub. Keywords: Al-qur’an, child development, role of father.